PEMODELAN MATEMATIKA PRODUK NANO SPRAY DAN MAGIC STICK PERUSAHAAN MILLIONAIRE CLUB INDONESIA (MCI) STOCKIST LAMPUNG - Reni Permata Sari; Ummi Rosyidah (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2020)
One of the companies engaged in beauty products is Millionaire Club Indonesia (MCI). The products offered are beauty products without chemicals and are certainly safe for women's bodies. The product is called Nano spray and Magic Stick. The MCI company applies a purchase order system in product marketing. So that the MCI company to stock the sales. Consumers can order in advance to get the goods. The purpose of this research is to find out the amount of fluctuation of Nano Spray and Magic Stick sales and to know the minimum purchase order of Nano Spray and Magic Stick in 2019 with mathematical modeling methods and linear programs. The results of the study are as follows: (1) There was a fluctuation (increase or decrease) in sales of Nano Spray and Magic Stick. Nano Spray sales are always more than Magic Stick sales. This proves that Nano Spray enthusiasts are more numerous than Magic Stick enthusiasts. Nano Spray and Magic Stick products, the most sales occurred in the month of 4 (April) and the lowest sales in the month of 12 (December). (2) The form of modeling to minimize Nano Spray and Magic Stick purchase orders in 2019 that is, for is the number of Nano Spray purchase orders in the month-to-month and is the number of Magic Stick purchase orders in the month-to-month. The minimum number of Nano Spray and Magic Stick purchase orders in 2019 is 15,552 units with the number of Nano Spray and Magic Stick purchase orders in 2019 respectively being 8337 units and 7215 units.